Pembiasaan literasi untuk meningkatkan keterampilan kognitif di MI Tarbiyatul Banin Banat Jetak Tuban - Rohmah, Pujiati (Maliki Interdisciplinary Journal, 2024)
Education is a crucial aspect in improving the quality of human life, especially in facing the Era of the Fourth Industrial Revolution. In this context, students’ cognitive abilities need to be enhanced through effective literacy education. This article discusses the provision of literacy education at MIS Tarbiyatul Banin Banat to improve students’ cognitive skills. This research employs a qualitative method with a population of 298 students from the 2023/2024 academic year. Data were obtained through observation and interviews and analyzed in-depth. The Qur’anic literacy program implemented includes the habit of reading short surahs from the 30th Juz of the Quran and daily prayers before the start of lessons and after congregational Dhuhr prayers. It is hoped that through this habit, students will be able to memorize and read Arabic texts fluently. Assessment is conducted through memorization tests by the class teacher. In conclusion, the habit of reading Qur’anic literacy at MIS Tarbiyatul Banin Banat can enhance the ability to read and memorize short surahs and daily prayers, while also fostering a love for and practice of the teachings of the Quran in daily life.